Dinamika dan problematika kebijakan pendidikan Islam di Indonesia - Rambe, Sari Madani; M, Amril (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study explores the dynamics and challenges of implementing Islamic education policies at various educational levels in Indonesia, from primary to higher education. Using a descriptive-qualitative approach, it analyzes how these policies contribute to national education goals and address structural issues. The findings show that despite systematic regulation, significant obstacles remain, including unequal distribution and quality of educators, disparities in facilities between urban and rural areas, unstable curricula, and weak institutional coordination. These problems are compounded by limited professional training and insufficient integration of Islamic values and religious moderation. The authors proposed solutions, such as digitalizing Islamic education, strengthening teacher competence, reforming context-based curriculum, and increasing community involvement. The study highlights the importance of participatory and locally responsive policy reform to improve the quality and relevance of Islamic education in Indonesia.